Gramática tradicional e tradição sociodiscursiva em gramáticas escolares de língua portuguesa da década de 2000 - Ribeiro, Natássia Thais do Nascimento (2021)
This dissertation aims to study Brazilian school grammars from the 2000s, from a historiographical perspective. The school grammars focus of this investigation were produced in a context in which, in Brazil, a change in the reflection on the teaching of the mother tongue had already taken place, from the consolidation of the sociodiscursive tradition (SDT) in the scope of Linguistic research in the 1990s (GUEIROS, 2019). Therefore, this research had as main objective to investigate how the consolidation of SDT in Brazil affected the production of school grammars of the 2000s, causing, in these linguistic instruments, movements to break with the epistemology of traditional grammar (TG) and consequent affiliation with SDT guidelines. This research is situated in the theoretical-methodological field of Historiography of Linguistics (HL), understood as an interdisciplinary area within the history of science and ideas (SWIGGERS, 2013), and it is anchored mainly in Koerner (1996), with the principles for the development of a work in HL, and Swiggers (2004, 2019), with the linguistic knowledge layers. Besides, it was also adopted the concepts of rupture rhetoric (MURRAY, 1994), grammatization (AUROUX, 2014) and the traditional grammatization paradigm (VIEIRA, 2018). The methodological undertaking, concerning the clipping of primary sources, had the following criteria: periodization (the 2000s); type of rhetoric (rupture / continuity); publishing (exclusion of repeated publishers); year of publication (most recent edition by each publisher) and more prototypical works by SDT and TG (one from each), both selected after previous reading, based on the analytical categories. After clipping, the grammars selected as primary sources were Gramática: uso e interação, by Laís B. de Carvalho (2006), and Minha gramática escolar, by Maria A. Cláudio (2007), which were respectively called G1 and G2 and analyzed using the following the categories: a) rupture rhetoric (MURRAY, 1994) and b) linguistic knowledge layers (SWIGGERS, 2004, 2019), in correlation with the five epistemological guidelines of traditional grammar (VIEIRA, 2020). The analysis of the presentation texts of the grammars showed that both mention the objects of SDT studies, thus demonstrating rhetoric of affiliation to this new tradition of linguistic studies and consequent rhetoric of rupture with the TG. About the analysis of the morphosyntax contents, the results pointed to movements of rupture with the TG and a consequent attempt to affiliate with the SDT guidelines in the two analyzed works, however, with significant differences between both. This is because, although both present rupture movements with the TG, G1 does it more effectively in relation to the G2, since these rupture movements are more prominent in the first concerning the five TG guidelines, reason for which G1 was considered more prototypical of SDT. G2, on the other hand, was considered to be more representative of TG, since it brings more prominent lines of continuity in relation to TG guidelines. Therefore, our conclusions indicate that, despite the attempt to break with the grammatical tradition, the two school grammars analyzed still present, even if in different proportions, lines of continuity with the epistemological guidelines of traditional grammar (VIEIRA, 2020), which does not allow us to speak of a break, in fact, with the grammatical tradition in the treatment of the contents of morphosyntax.